Pengaruh Kepemimpinan Transformasional Dan Lingkungan Kerja Nonfisik Terhadap Kinerja Karyawan Panen Di Pt Nusa Pusaka Kencana Kebun Bahilang - Bukhori, M. Agustian; Djaingsastro, Aulia Djuanda; Aznur, Tifany Zia (Lembaga Teewan Journal Solutions, 2026)
This study aims to analyze the influence of transformational leadership and the non-physical work environment on the performance of harvest employees at PT Nusa Pusaka Kencana Bahilang Estate. The study was motivated by differences in productivity among harvest employees, which may be influenced by leadership practices and workplace conditions. It is based on Human Resource Management theory, which emphasizes that transformational leadership and a supportive non-physical work environment are essential factors in improving employee performance. This research employed a quantitative approach with a causal associative design. The sample consisted of 49 harvest employees selected using a saturated sampling technique. Data were collected through questionnaires and interviews and analyzed using multiple linear regression with SPSS 21. The results indicate that transformational leadership has a positive and significant effect on employee performance (β = 0.640; t = 4.933; p = 0.000). Likewise, the non-physical work environment has a positive and significant effect on employee performance (β = 0.663; t = 4.561; p = 0.000). Simultaneously, both variables significantly affect employee performance (F = 19.751; p = 0.000). The coefficient of determination (R² = 0.462) indicates that 46.2% of the variation in employee performance is explained by these variables, while the remaining 53.8% is influenced by other factors. The findings suggest that strengthening transformational leadership and fostering a supportive non-physical work environment can sustainably improve harvest employee performance.